O Governo Bolsonaro e a Folha de São Paulo: uma análise dos três primeiros meses de governo - Mesquita, Mariana Gonçalves de (Universidade Federal de São Carlos, 2021)
Communication and politics are terms in confluence. Specifically, traditional communication vehicles, such as written newspapers, have a great influence on public opinion, as they are responsible for guiding discussions in the media and in the public sphere. It is no different in Brazil and one of the vehicles that carry this role in its history and circulation is Folha de São Paulo (FSP). Based on this context, the objective of this research is to understand how the FSP opinion section dealt with the first three months of the Jair Bolsonaro Government from the perspective of the study of framing theory, which is responsible for the central idea that organizes reality within certain axes of appreciation and understanding. The question underlying the survey is how Folha de São Paulo portrayed Jair Bolsonaro's government in its opinion section in the first 3 months of government, called honeymoon. The hypothesis for this question is that there was no truce period between the vehicle and the Government, as the two are ideologically out of line and, therefore, coverage was predominantly made with negative valences. Except for the coverage of economic agendas, where both the Government and the vehicle are positioned as liberal. The data presented reveal that this predominance was based on the analysis of the leaders involved and their respective agendas, in addition to a considerable proportion of content aimed at criticizing the Government.
The Bolsonaro's Government and Folha de São Paulo: analysis of the first three months of government
Keywords: Comunicação política; Imprensa; Folha de São Paulo (Jornal); Governo Bolsonaro; Political communication; Press; Bolsonaro's Government; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO